2018
DOI: 10.3389/fimmu.2018.01254
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Glycan Shedding in the Blood: New Class of Multiple Sclerosis Biomarkers?

Abstract: IntroductionMultiple sclerosis (MS) is a devastating autoimmune disease, afflicting people in the prime of their lives. Presently, after initial clinical presentation, there are no reliable markers for whether a patient will develop MS, or whether their prognosis will be aggressive or relapsing–remitting. Furthermore, many MS patients do not respond to treatment. Thus, markers for diagnosis, prognosis, and treatment-responsiveness are lacking for a disease, where a precision medicine approach would be valuable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…Another previous study showed enhanced leukocyte adhesion in the retina of knockout mice for syndecan 1, a component of the EG 27 . In addition, several studies have shown degradation of the EG in diseases characterized by decreased CBF, such as malaria infection, multiple sclerosis, and stroke 28,29,30 . Based on these previous studies and our results, we suggest that the loss of the EG in capillaries, caused by the pathological progression of SVaD, may induce greater leukocyte adhesion to the vascular endothelium and, thereby, promote capillary stalling.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study showed enhanced leukocyte adhesion in the retina of knockout mice for syndecan 1, a component of the EG 27 . In addition, several studies have shown degradation of the EG in diseases characterized by decreased CBF, such as malaria infection, multiple sclerosis, and stroke 28,29,30 . Based on these previous studies and our results, we suggest that the loss of the EG in capillaries, caused by the pathological progression of SVaD, may induce greater leukocyte adhesion to the vascular endothelium and, thereby, promote capillary stalling.…”
Section: Discussionmentioning
confidence: 99%
“…While small dyes such as fluorescein (376 daltons) and Alexa Fluor (643 daltons) permeate the glycocalyx, dextrans (40–150 kD) penetrate <60% of its volume (Kutuzov et al, 2018). In disease, glycocalyx degradation is associated with more severe BBB leakage in models of multiple sclerosis (MS) and cardiac arrest (DellaValle et al, 2018; Zhu et al, 2018).…”
Section: The Nvumentioning
confidence: 99%
“…Two microlitres of plasma was dotted in duplicate on nylon membranes (Hybond N + , Amersham, RPN203B) similar to. 5 Membranes were blocked in blocking buffer (5% skim milk+TBS-0.05%Tween20) and incubated overnight at 4°C in blocking buffer+primary antibody, washed (TBS-0.05%Tween20), incubated with blocking buffer+secondary antibody, washed, incubated with SuperSignal Femto Reagent (Thermo Scientific), imaged with CCD camera (LAS 4000, GE), analyzed with ImageJ 6 for raw integrated density, and transformed by a factor of 10 −5 . Primary antibody targets: glycosaminoglycans (GAGs): chondroitin sulfate (CS, Sigma), heparan sulfate (HS, Millipore), keratan sulfate (KS, US-Biologicals), and hyaluronic acid (HA, Bio-Rad); and proteoglycans (PGs): CD44 (DAKO), syndecan (Syn)-1 (R&D), 2 (R&D), 3 (R&D), 4 (Santa Cruz), glypican-1 (R&D), and BiGlycan (Abcam).…”
Section: Plasma Glx Analysismentioning
confidence: 99%